Increasing the sensitivity of 2D high-resolution NMR methods applied to quadrupolar nuclei - Amoureux, J. P.; Delevoye, L.; Steuernagel, S.; Gan, Zhengting; Ganapathy, Subramanian; Montagne, L. (Journal of Magnetic Resonance, 2005)
Gan and Kwak recently proposed a soft-pulse added mixing (SPAM) idea in the classical two-pulse multiple-quantum magic-angle spinning scheme. In the SPAM method, a soft pi/2 pulse is added after the second hard-pulse (conversion pulse) and all coherence orders in between them are constructively used to obtain the signal. We, here, further extend this idea to distributed samples where the signal mainly results from echo pathways and that from anti-echo pathways dies Out after a few t(1) increments. We show that, with a combination of SPAM and collection of fewer anti-echoes, an enhancement of the signal to noise ratio by a factor of ca. 3 may be obtained over the z-filtered version. This may prove to be useful even for samples with long T'(2) relaxation times. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: high-resolution; quadrupolar nuclei; sensitivity; Solid-state NMR

Identification of sublattice damages in swift heavy ion irradiated N-doped 6H-SiC polytype studied by solid state NMR - Viswanathan, E.; Kanjilal, D.; Sivaji, K.; Ganapathy, Subramanian (Journal of Physical Chemistry B, 2011)
We have studied N-doped 6H-SiC in its pristine and Swift Heavy Ion (SHI) irradiated (150 MeV Ag12+ ions) forms by solid state Nuclear Magnetic Resonance (NMR) at 7.01 T using C-13 and Si-29 as probe nuclei under magic angle spinning. We show that increased levels of nitrogen doping, than used before, lead to the observation of Knight shifts emanating from an increase in electron density in the conduction band, which in C-13 far exceed those in Si-29 MAS spectra. We have rationalized the differential effects in the MAS spectra and site-dependent paramagnetic shifts in terms of the nitrogen doping at the A, B, and C lattice sites. N-doping has a profound effect on Si-29 spin-lattice relaxation, and the site-dependent relaxation behavior is attributed to a difference in conduction electron properties at the different lattice sites. Si-29 T-1 measurements serve to identify the sublattice damages in SHI irradiated 6H-SiC. By determining the spin-lattice relaxation rates as a function of the SHI irradiation ion fluences, the change in relaxation behavior is correlated to the damage production mechanism. The sublattice damage leads to discernable changes in the interaction between the mobile unpaired electrons in the conduction band and the nuclear site, which profoundly influence the NMR relaxation properties. Our relaxation studies also provide evidence for site-dependent localized effects and a decrease in carrier spin density in the conduction band for the SHI irradiated 6H-SiC.